Antibacterial Activity of Streptomyces sp. Isolated from High Tolerant Ecosystem in Babylon Province, Iraq (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
The goal of this research is producing antibiotic from two Actynomycites species  isolated from the high tolerant ecosystem, isolate from high salty soil and high alkaloid soil, used whey and yeast extract medium as a perfect medium for culturing (1% glucose, 1% trypton, 0.092% glycine, 0.004% HCl and 8.5 PH), perfect incubation circumstances are 30 C0 in 4 days, the infiltrate of crude antibiotic concentrate by using a rotary evaporator, then extract the antibiotic from concentrate infiltrate with ethanol: methanol: ethyl acetate methods ( 50:30:20 Vol), drying the extract at 30 C0 to dissolve both antibiotic in distilled water with three concentration ( 50, 75, 100 µg/ml) and disinfectant by 0.45 Millipore.Antibiotic activity from two isolates of Streptomyces sp.  were measured against positive and negative control bacteria (Escherichia coli, Bacillus subtilis, streptococcus pyogenes and staphylococcus aureus) by well diffusion method, the results show the antibiotic produced by isolating No. 2 active against E. coli, S. aureus and S. pyogenes  while the isolating No. 1 was active only against E. coli and no activity against gram-positive bacteria.Extract component was separated with TLC technique (thin layer chromatography) by using silica gel 20*20cm with high polar mix (7 water: 5 acetic acid: 3 biotanol vol.) according to relative factor Rf  for antibiotic, isolate No.1 give 0.6 Rf  for one antibiotic and isolate No.2  give 0.15 Rf  for two antibiotics against S. aureus  and the other one with 0.45 Rf  against E. coli and S. pyogenes, means these antibiotic has synergism activity.